Exploring the potential of Metaverse: The transformation of social interaction in distance learning - Lisna Dwi Astuti; Salma Ambar Sunni Syahbana; Muhammad Nazuar (Himpunan Pengembang Kurikulum Indonesia, 2024)
Distance learning has become a new educational paradigm, especially with the ever-evolving technology. One of them is the metaverse, a virtual world that allows users to interact with virtual environments and objects and other users. This study aims to determine the use of metaverse for social interaction during distance learning (online) through a literature review. The method used in this research is a literature study. The existence of Metaverse in education is both an opportunity and a challenge. Learning using Metaverse can provide new experiences for students and is not limited by space and time. Metaverse can be used in distance learning to improve social interaction between students and teachers, as well as between students with each other. It is hoped that this article can provide insight into the potential of Metaverse in transforming social interaction in distance learning. Abstrak Pembelajaran jarak jauh telah menjadi suatu paradigma baru dalam dunia pendidikan, terutama dengan teknologi yang terus berkembang. Salah satunya Metaverse yang merupakan dunia virtual sehingga memungkinkan pengguna untuk berinteraksi dengan lingkungan dan objek virtual serta dengan pengguna lainnya. Penelitian ini bertujuan untuk mengetahui penggunaan Metaverse terhadap interaksi sosial saat pembelajaran jarak jauh (online) melalui tinjauan literatur. Metode yang digunakan pada penelitian ini yaitu studi literatur. Keberadaan Metaverse dalam dunia pendidikan menjadi peluang sekaligus tantangan. Pembelajaran menggunakan Metaverse dapat memberikan pengalaman baru untuk peserta didik dan tidak terbatas oleh ruang serta waktu. Metaverse dapat digunakan dalam pembelajaran jarak jauh untuk meningkatkan interaksi sosial antara peserta didik dan guru, serta antara peserta didik satu sama lain. Diharapkan artikel ini dapat memberikan wawasan tentang potensi Metaverse dalam transformasi interaksi sosial dalam pembelajaran jarak jauh. Kata Kunci: interaksi sosial; Metaverse; pembelajaran jarak jauh